Creating Engaging Powerpoint Supplementary Materials for Twelfth-Grade Students: Enhancing Procedure Text Learning - Anjelli Milleni; Ikhsanudin Ikhsanudin; Surmiyati Surmiyati (Journal of English Education Program, 2023)
This research aimed to find the students’ needs and to design PowerPoint-based supplementary materials to teach writing procedure text for twelfth-grade students of a private school in Kalimantan Barat Province. In conducting this research and development (R&D), the researcher applied the ADDIE procedure, which focused on ADD steps (analysis, design, and development). The participants of this research were an English teacher and 21 twelfth-grade social science students. The instruments used to collect the data were questionnaires and an unstructured interview sheet. The result of the needs analysis showed that the students needed various contents of writing procedure text in the form of PowerPoint. Moreover, the result of the internal evaluation showed that a design of supplementary materials of procedure text in PowerPoint scored high for all the criteria of material (89.8%) and media (83.3%). In conclusion, the design of supplementary materials for writing procedure text in PowerPoint was appropriate to implement.